Awesome purpose - MacLennan, Nigel 1961- (Gower, 1999)
Taken as a whole, this book provides a step-by-step guide to achieving culture change and alignment through the application of three innovative models - the CAM, the 9R Model and the 6P Model. Business leaders and organization development specialists alike will find clear and innovative material in this book to stimulate and inspire them. They will find that they are provided with the tools to align their organization and inspire their staff to performance levels not possible without an awesome purpose.